Public Understanding of Tourism Communication in the Coastal Region of Southeast Sulawesi - Harnina Ridwan; Marsuki Iswandi; Jamaluddin Hos; Muh. Najib Husain (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
Known as a coastal area, Southeast Sulawesi saving potential coastal tourism-oriented by the local community but has not been utilized fully, because people in coastal areas do not have the financial capacity and expertise to manage or involved in nature-based tourism activities directly. Research was done by qualitative approach to describe, formulate and analyze the phenomenon of tourism communications in coastal areas of Southeast Sulawesi. The location of research was done in Southeast Sulawesi province in 2019 on coastal of Pantai Toronipa, coastal of Pantai Nirvana, and the coastal of Pantai Nambo. Research’s Informants consisted of the local community, business tourism services, and tourism activist groups. Data collection techniques are done by observation, in-depth interviews, and documentation. The research’s results showed the coastal area in Southeast Sulawesi has been formed the society’s understandings of tourism by itself. There are three groups of society, First group are the ordinary people who understand that tourism only a part of recreation, leisurely stroll, traveling, etc; The second group also consists of (a) intelligent tourism consumer group, and (b) the group of exploration and exploitation destinations for business purposes. The third group is a group of activists who know tourism significantly, guide destinations, human resources, and traditional institutions to strengthen community substance as excellent destinations sustainably.